Design and Test of Portable Hyperspectral Imaging Spectrometer. (27th August 2017) - Zou, Chunbo; Yang, Jianfeng; Wu, Dengshan; Zhao, Qiang; Gan, Yuquan; Fu, Di; Yang, Fanchao; Liu, Hong; Bai, Qinglan; Hu, Bingliang
Abstract : We design and implement a portable hyperspectral imaging spectrometer, which has high spectral resolution, high spatial resolution, small volume, and low weight. The flight test has been conducted, and the hyperspectral images are acquired successfully. To achieve high performance, small volume, and regular appearance, an improved Dyson structure is designed and used in the hyperspectral imaging spectrometer. The hyperspectral imaging spectrometer is suitable for the small platform such as CubeSat and UAV (unmanned aerial vehicle), and it is also convenient to use for hyperspectral imaging acquiring in the laboratory and the field.